2006
DOI: 10.1308/003588406x82943
|View full text |Cite
|
Sign up to set email alerts
|

Are National Guidelines for Total Hip Replacement in the UK Reflected in Practice?

Abstract: Consensus was observed in several areas including the use of pre-admission clinics and modern cementing techniques. Facilities deemed necessary for THR surgery such as HDU/ITU back-up, ultra-clean air and dedicated orthopaedic wards are almost universally available. However, a lack of consensus is evident in many areas including the process of obtaining written consent, thrombo-embolic prophylaxis, duration of antibiotic prophylaxis, supervision of trainee surgeons and follow-up arrangements. The proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Over the last 3 decades, the threshold for total hip arthroplasty (THA) has been lowered to include younger and more physically demanding patients ( Abraham et al 2006 , Treacy 2006 ). However, hip arthroplasty surgery in younger patients with more demanding lifestyles has been reported to fail earlier ( Tennent and Goddard 2000 , Lewthwaite et al 2008 , Howcroft et al 2008 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 3 decades, the threshold for total hip arthroplasty (THA) has been lowered to include younger and more physically demanding patients ( Abraham et al 2006 , Treacy 2006 ). However, hip arthroplasty surgery in younger patients with more demanding lifestyles has been reported to fail earlier ( Tennent and Goddard 2000 , Lewthwaite et al 2008 , Howcroft et al 2008 ).…”
mentioning
confidence: 99%
“…In order to address this issue, some surgeons have advocated the use of metal-on-metal or ceramic bearing surfaces with cementless porous coated prostheses to reduce implant surface wear rates and bone loss in younger osteoarthritics ( Shetty and Villar 2006 ). Other surgeons have advocated hip resurfacing (HRS) for young patients ( Harty et al 2005 , Abraham et al 2006 , Bengs et al 2008 , Greene et al 2009 ).…”
mentioning
confidence: 99%
“…Exceptionally, one study in Korea showed very poor accordance with published guidelines for antibiotic prophylaxis [25]. Other studies that evaluated guideline adherence for the use of prophylactic antibiotics in THR or TKR procedures in different regions reported adherence rates that ranged from 36.3% to 66.9% [26–30]. In comparison, the guideline adherence rate in Taiwan is relatively low; however, the stable increase in guideline adherence rates after its introduction is a promising phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of members of the British Orthopaedic Association showed widespread use of thromboprophylaxis but no apparent compliance with guidelines. 9 Many readers will recognise from their own practice, from audit of their institution's practice or from discussions with colleagues, that guidelines are not routinely followed.…”
Section: Are Guidelines Followed?mentioning
confidence: 99%